Interlace polynomials of lollipop and tadpole graphs - Christina L Eubanks-Turner; Kathryn Cole; Megan Lee (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2022)
In this paper, we examine interlace polynomials of lollipop andtadpole graphs. The lollipop and tadpole graphs are similar in that they bothinclude a path attached to a graph by a single vertex. In this paper we giveboth explicit and recursive formulas for each graph, which extends the work ofArratia, Bollobas and Sorkin, among others. We also give special values,examine adjacency matrices and behavior of coecients of these polynomials.